The Role of Chiefs in Land Management in Peri-Urban Customary Areas Of Blantyre, Malawi: The Case of Mpemba - Magwede, Chimwemwe Edith (University of the Witwatersrand, Johannesburg, 2022)
Peri-urbanisation is a new form of urbanisation and the peri-urban area is a new kind of multi-functional landscape for urban development. How peri-urban areas are managed matters because they are close to the city and due to high urbanisation rates in most developing countries, these areas will soon be part of the city. If urban peripheries are not well-managed, they will be a challenge for sustainable development. In Malawi, peri-urban areas fall under customary land and chiefs are the custodians of customary land. The study unpacks the role of chiefs in land management, how the National Land Policy and land-related legislation position customary leadership in the governance of land management and how municipal and customary land management systems interact with each other in the peri-urban areas. The study employed a qualitative approach. Semi-structured interviews were conducted and policy and legislation were reviewed. The 2002 National Land Policy of Malawi and land-related legislation were reviewed focusing on the role of chiefs in land management. Although the peri-urban areas fall under the jurisdiction of chiefs, the research reveals that this area is treated as no man's land as there exists an overlap of authorities in the peri-urban areas. The chiefs witness land transactions, advise their people on how to secure their land, and partially guide and manage land, although they are not aware of land regulations and standards. The findings also disclose that there is a lack of coordination within municipal land management systems and between municipal land management systems and customary land management systems. Although the legislation states that chiefs have to be incorporated in land management, these laws have not been fully implemented as there are still in the pilot phase.
A research report submitted in partial fulfilment of the requirements of the degree of Masters in Urban Studies (Housing and Human Settlements). to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, at the University of Witwatersrand, Johannesburg (Republic of South Africa), 2022.
Keywords: Peri-urbanisation; Peri-urban areas; Land management; Customary land management; Municipal land management systems; Sustainable urbanization; UCTD; SDG-9: Industry, innovation and infrastructure